1127 Utility of Quantitative EEG During Sleep as a Potential Biomarker of Lewy Body Disease Progression. (27th May 2020) - Matar, E; Ehgoetz Martens, K A; Grunstein, R R; D'Rozario, A; Lewis, S J
Abstract: Introduction: Sleep disturbances are common among patients with Lewy body disorders. Idiopathic REM sleep behavior disorder (iRBD) has been identified as a prodromal Lewy body condition with a significantly increased risk of conversion to either Parkinson's disease (PD) or Dementia with Lewy Bodies (DLB). Pathological involvement of thalamic and brainstem structures involved in sleep regulation has been reported in these disorders, especially in later stages. We hypothesized that progression along the Lewy body disease spectrum may be associated with unique changes in spindle density and EEG power spectra during sleep reflecting involvement of these deep brain structures. Methods: A cross-sectional design was used. 9 polysomnography confirmed iRBD, 18 early PD, 23 DLB and 13 controls underwent overnight polysomnography, neurological and neuropsychological assessment. Power spectrum analysis during NREM and REM sleep was undertaken using a previously validated quantitative EEG algorithm and compared between groups. Following artefact and outlier removal, results were analysed using the Cz derivation. Groups were statistically compared with a non-parametric Jonckheree-Terpstra test for ordered alternatives, controlling for age and sex. Results: We found a significant and ordered reduction in power in the spindle frequency band (12-15 Hz) in NREM sleep across the Lewy body disease spectrum compared to controls (Controls > iRBD > early PD > DLB; T JT = 521.00, z = -2.902. p <0.001). In REM sleep we found a shift in power to slower frequencies with increased power in the theta (4.5-8 Hz) band in order of disease severity (DLB > early PD > iRBD > Controls; T JT = 950.00, z = 2.253. p =0.024). No differences were found across the other frequency bands in NREM or REM sleep. Conclusion: There is a significant and progressive reduction in spindle density and corresponding slowing in REM sleep frequencies during sleep with clinical Lewy body staging. Thus, such measures have the potential to be useful biomarkers of progression towards Lewy body dementia from prodromal stages. Support: This work was supported by a NHMRC Dementia Team Grant (#1095127), the NHMRC Postgraduate Scholarship and the University of Sydney Research Excellence Initiative 2020 grant.